Cold War conflicts and the USCG Afetna Point LORAN station in Saipan, CNMI. Issue 2 (4th May 2022) - Dixon, Boyd
ABSTRACT: This study focuses on the US Coast Guard LORAN station at Afetna Point in Saipan, Commonwealth of the Northern Mariana Islands, to discern what social impact the Cold War facility and servicemen had on the local community. Archaeological and archival investigations indicate that the facility was built a few months after the American WWII invasion of Japanese-held Saipan in June 1944. Oral histories gathered from senior members of the indigenous Chamorro community in the village of San Antonio revealed that the station and US Coast Guard service members played a complex and vital role in the social and economic life of the local community during the Cold War.